ANALISIS KEPUASAN PELANGGAN TERHADAP PELAYANAN PT. AMARTHA MANUNGGAL PRIMA (ID EXPRESS) MEDAN JOHOR DENGAN METODE SERVICE QUALITY - Syahru Romadhon; Rizkha Rida; Muhammad Fiza Lubis; Rizal Abdul Khoir (Bajang Institute, 2025)
This research analyzes the level of customer satisfaction at PT. Amartha Manunggal Prima uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) indices. The research results show that customers are satisfied with the company's services, with the tangible, responsiveness, reliability, assurance and empathy dimensions reaching 81%, 81%, 81%, 82% and 80% respectively. Assurance has the most significant influence on customer satisfaction, reflecting high satisfaction with facilities and other physical aspects. Analysis of the level of conformity between customer expectations and service performance shows that the company has fulfilled customer expectations well. The tangible dimension reached 85.51%, responsiveness 87.18%, reliability 85.25%, assurance 86.69%, and empathy 86.09%. The IPA results identify priority improvements in all dimensions of service quality, with a focus on the use of advanced technology and timeliness of service. Customers expect technological innovation to increase efficiency, accuracy and speed of service, as well as on-time delivery according to promised schedules. This research suggests that companies need to optimize operational processes, including better scheduling, effective inventory management, and improved logistics systems to reduce waiting times and increase service efficiency.